Semi‐automated quantification of geographic atrophy with blue‐light autofluorescence and spectral‐domain optical coherence tomography: a comparison between the region finder and the advanced retinal pigment epithelium tool in the clinical setting. Issue 6 (24th March 2019) - Reumueller, Adrian; Sacu, Stefan; Karantonis, Maria Georgia; Steiner, Irene; Weigert, Guenther; Schmidt‐Erfurth, Ursula
Abstract: Purpose: To compare inter‐ and intraobserver reliability and intermodality agreement on quantification of geographic atrophy, using two routinely available quantification tools, based on blue‐light fundus autofluorescence (BAF) and spectral‐domain optical coherence tomography (SD‐OCT). Methods: Quantifications of atrophic lesions within the central 5 mm of 30 eyes from 30 patients (mean age: 76.1 years) were independently performed by two clinicians on BAF images using the region finder (RF; Heidelberg Engineering) and on SD‐OCT using the advanced retinal pigment epithelium tool (ARPET; Carl Zeiss Meditec) at baseline and follow‐up (mean interval: 336 days). Inter‐ and intraobserver reliability was determined by intraclass correlation coefficients (ICC) and Bland–Altmann plots. Additionally, graders rated the experienced difficulty of each measurement. Results: Intraclass correlation coefficients (ICC) showed excellent inter‐ and intraobserver reliability with values between 0.994 and 0.998 for RF and slightly higher values for ARPET of 0.997 and 0.999. Bland–Altman plots showed smaller variability for ARPET. Mean interobserver differences (95% CI) for size measurements were −0.11 (−0.27; 0.05) (baseline) and −0.05 mm² (−0.18; 0.08) (follow‐up) for RF and −0.04 (−0.14; 0.06) and −0.06 mm² (−0.14; 0.02) for ARPET. Measurements of lesions were on average 0.57 mm² (0.35; 0.79) or 7.6% larger in ARPET. Lesion size between graders did not differ significantly. There was no statistically significant difference in relative enlargement rates between methods. There was poor to moderate agreement between graders when rating the experienced difficulty of each measurement. Conclusion: Semi‐automated analysis of geographic atrophy with RF and ARPET is equally reliable and reproducible in clinical settings, despite both algorithms require frequent adjustment by users. The ARPET restricts size measurements to the central 5 mm, which limits its ability to fully track GA progression. Results of both tools are not interchangeable as measurements with ARPET result in larger lesion sizes.